The role of peace educators in building a culture of peace in the school: Comparisons between Indonesia and Malaysia - Wahyu Nanda Eka Saputra; Trikinasih Handayani; Agus Supriyanto; Waharjani Waharjani; Salleh Amat; Arif Budi Prasetya; Prima Suci Rohmadheny; Yuliyanti Indriani Rahayu (Institute of Advanced Engineering and Science, 2024)
A culture of peace is a condition that school members covet. Indonesia and Malaysia are two neighboring countries that support implementing peace education. Even though the two countries are allied and neighbors, each country has uniqueness, including implementing peace education. This study aims to describe the role of peace educators in Indonesian and Malaysian schools. Systematic literature reviews identify the position of peace educators in building a culture of peace in schools. The study uses eight main articles to describe the role of peace educators in Indonesia and Malaysia. The selected articles were analyzed by data extraction. The study results show that peace educators in Indonesia and Malaysia have different characteristics. Peace educators in Indonesia focus more on efforts to suppress student violence. Meanwhile, peace educators in Malaysia focus on building a constructive mindset towards all forms of experiences experienced by students. The study recommends further research to create a unique model of peace education according to the characteristics of students in Indonesia and Malaysia.